Determining the fate of selenium in wheat biofortification: an isotopically labelled field trial study - Mathers, Andrew W.; Young, Scott D.; McGrath, Simon; Zhao, Fang-Jie; Crout, Neil M.J.; Bailey, Elizabeth H. (Springer, 2017)
Aims The principal aim of this research was to quantify retention of a single, realistic Se biofortification application (10 g ha-1) in contrasting soils over two growing seasons utilizing an enriched stable Se isotope (77Se) to discriminate between applied Se and native soil Se. Methods Isotopically enriched 77Se (Na2SeO4) was applied (10 g ha-1) to four replicate plots (2 m x 2 m) of winter wheat, on three contrasting soils on the University of Nottingham farm (UK), at early stem extension in May 2012. Labelled 77Se was assayed in soil and crop fractions by ICP-MS. Results Topsoil retained a proportion of applied Se at harvest (c. 15 – 31 %) with only minor retention in subsoil (2-4 %), although losses were 37 – 43 %. Further analysis of topsoil 77Se, the following spring, and at second harvest, suggested that labelled Se retained in soil was25 fixed and uptake by a following crop was negligible. Conclusions Prolonged biofortification leads to accumulation of Se in soil but the retained Se has very low bioavailability and mobility. The time required to double the soil Se content would be about 500 years. However, reincorporation of cereal straw could provide a residual source of Se for a following crop, depending on timing and management.